Complete Pathological Response in Stage IV Rectal Carcinoma: Proper Planning and Place is a Key - Deep Lamichhane; Suraj Suwal; Resham Rana; Shweta Baral; Rishikesh Narayan Shrestha (National Cancer Center - Dharmais Cancer Hospital, 2022)
Introduction: Liver metastasis is frequently encountered in patients with rectal cancer; it can be synchronous or metachronous. Some selected patients can be treated with curative intent using multimodality therapy under the care of a dedicated team in a comprehensive cancer center. However, the treatment is long and tiring for the treating team, the patient, and the relatives. Treatment is difficult to execute in a country like ours with a limited number of cancer centers. We present a patient from a remote village with stage IV disease, who completed all modalities of treatment with a favorable outcome. Case Presentation: A fifty-five-year-old man from a remote village presented to us with a complaint of per rectal bleeding. He was diagnosed with rectal carcinoma with solitary liver metastases. He received multimodality treatment in the form of chemotherapy, radiotherapy, and surgery. He attained a complete pathological response at both primary and metastatic sites.Conclusions: Good outcomes can be achieved in selected stage IV rectal cancer. This requires multimodality treatment and a proper plan, preferably in a comprehensive cancer center